Diplomatic Engagement and Economic Influence: The Interplay of Chinese OFDI and High-Level Visits - Youngjun Choi; Jiaen Li (East Asian Economic Review)
This study investigates the interdependence between Chinese outward foreign direct investment (OFDI) and high-level visits. Using a simultaneous equation model (SEM) and Three-Stage Least Squares (3SLS), we analyze a panel dataset comprising 146 host countries over the period 2003 to 2021, covering the tenures of Presidents Hu Jintao and Xi Jinping. We further explore how the relationship between OFDI and diplomatic visits differs across developing and developed countries, as well as how shifts in political leadership influence these dynamics. Our empirical findings reveal a robust interdependence between China’s economic actions and diplomatic engagements. Specifically, there is a strong mutual influence between OFDI and visits to developing countries. In contrast, while visits positively impact OFDI in developed countries, there is no reciprocal influence. Moreover, the interdependence between OFDI and visits was particularly evident during President Xi’s tenure, whereas no such relationship was established during President Hu’s tenure. Our findings emphasize the importance of high-level visits in driving OFDI and highlight the critical role of economic engagement in achieving diplomatic goals. Furthermore, by examining this relationship across two presidential tenures, we offer a nuanced perspective on how host country characteristics and leadership transitions shape the dynamics between OFDI and diplomatic visits.